Variacion anatomica de la madera de Avicennia germinans en la laguna de La Mancha, Veracruz, Mexico - Yañez Espinoza, L.=700 1 Angeles, G.; Lopez Portillo, J.; Barrales, S.
(Es, En)
Ilus., 44 ref.
Keywords: ANATOMIA DE LA MADERA; XILEMA; AVICENNIA; MANGLES; SALINIDAD; MEXICO; SOCIEDAD BOTANICA DE MEXICO